The Effect of Co-Branding, Customer-Based Brand-Equity, and Packaging on Purchase Decision (Study on Purchasing Serum Azarine Cosmetic Marvel Edition) - Rizaldi Anggito Yudha; Restu Frida Utami; Herni Justiana Astuti; Suyoto Suyoto (Universitas Negeri Semarang, 2023)
The purpose of this research is to determine the influence of co-branding, customer-based brand equity, and packaging on purchasing decisions. To collect and study data, researchers used quantitative research methodology. Multiple linear regression analysis is the data analysis method used in this research, allowing researchers to investigate the influence between relevant variables. The sample obtained consisted of 102 respondents, but during distribution there were 2 data that were damaged, so only 100 respondents were used, which was distributed using Google Form via direct message Instagram users of Azarine Cosmetic Marvel Edition Serum, where the sample selection used a purposive sampling technique where they were selected based on standards. certain. The results of the analysis show that customer-based brand equity and packaging have a positive and significant effect on purchasing decisions, while co-branding has an insignificant negative effect on purchasing decisions for Azarine Cosmetic Marvel Edition. Specifically, the study found that the combined impact of co-branding, customer-based brand equity, and packaging accounted for 44.7% of the variability in purchasing decisions.